Primary education quality in sub-Saharan Africa : Three essays on improving student achievement - (:unkn) unknown (My University, 2024)
Over the past decades, primary school enrollment has significantly increased in Sub-Saharan Africa. Nevertheless, a large proportion of students do not master basic skills (reading, writing, arithmetic) by the end of the primary cycle. To improve student learning, numerous studies have focused on teacher quality or school governance. The objective of this thesis is to advance the understanding of education quality and student achievement through three distinct studies.The first focuses on the role of school principals and their involvement in school management. The results show that the involvement of school principals has no impact on student achievement, and that other characteristics, such as leadership,might play a more important role. The second chapter examines the competency-based reforms that have changed teaching practices in many Francophone African countries. This study shows that the competency-based approach has a positive impact on students’ language test scores. Finally, the last study analyzes the relationship between teacher contract types and student outcomes. The results suggest that contract teachers are as effective as tenured teachers, and that the type of teacher contract may not significantly impact student outcomes.
Keywords: African Research